PENGGUNAAN LAHAN BEKAS TANAM PALAWIJA DAN KOMPOSISI PUPUK TERHADAP PERTUMBUHAN DAN HASIL PRODUKSI PADI (Oryza sativa L) - Sahbudin Sahbudin; Suwandi Suwandi; Rossyda Priyadarshini (Plumula : Berkala Ilmiah Agroteknologi, 2018)
This research uses the design of the plot divided with the treatment of ex- planting is the main plot whereas the other treatment is a subplot consisting of 2 (two) factors and repeated 3 times. The first factor is rotation of Soybean-Rice and Corn-Rice Planting. The second factor was treatment of fertilizer composition, P0 (control), P1 (100% compost), P2 (50% compost + 50% N inorganic), P3 (75% compost + 25% N inorganic). The treatment (L2P1) yielded the highest 1000 grain weight of 25.28 g, L2P3 yielded the highest amylose content of 20.51%, L1P0 resulted in amylopectin content of 58.42%. The treatment of L2 resulted in 0.92 kg dry weight of dry paddy grain, yield 1000 grains weighing 25.10g, 19.23% amylose and L1 treatment yield the highest amylopectin content of 54.39%. The treatment (P2) resulted in the highest plant length of 102.67cm, P1 yielding 1000 grains of 24.36g, P3 yield amylose content of 20.00%, P0 yielding amylopectin content of 57.72%.